THE BOLC FOR LEGAL TRANSLATIONS: A TRIAL LESSON - GIAMPIERI, Patrizia (Comparative Legilinguistics, 2019)
This paper will explore how consulting the BoLC (Bononia Legal Corpus; Rossini Favretti, Tamburini and Martelli 2007) can be helpful and advantageous when tackling legal translations. To this aim, a 4-hour trial lesson with experienced translators was organized. Before the workshop, the participants translated a 300-word legal document issued within a civil case. Their translations (from English to Italian) were revised during the trial lesson, where the attendants learned how to consult the BoLC. They also used supplementary online resources, such as dictionaries and/or experts' blogs or fora. The paper findings will remark that despite some drawbacks, such as the absence of POS tagging and lemmatization, and a quite complex search syntax, the BoLC helps dispel doubts and deliver outstanding translation work. Its main usefulness lies in the possibility to find formulaic expressions and collocational use, which can be rather intricate in legal discourse.